2010
DOI: 10.1007/s11367-010-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of life cycle assessment and data envelopment analysis as a methodological approach for the assessment of fisheries

Abstract: Background, aim, and scope The synergistic use of life cycle assessment (LCA) and data envelopment analysis (DEA) is proposed as a new methodological approach to link environmental and socioeconomic assessments of fisheries. Therefore, the goal is to combine LCA and DEA in order to increase the assessment ability of both tools when applied to these fisheries. Specifically, the joint inclusion of economic aspects and the consideration of currently underrepresented environmental impact categories are tackled. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 25 publications
1
58
0
3
Order By: Relevance
“…DEA method'' approach, which combines environmental LCA with data envelopment analysis (DEA), a linear programming method, suggest that fleets with increased energy demand have a higher operational efficiency and, therefore, less space for minimization of operational inputs and environmental impact reductions (Vázquez-Rowe et al 2010b, 2011b.…”
Section: Comparison Between the Assessed Fishing Fleetsmentioning
confidence: 99%
“…DEA method'' approach, which combines environmental LCA with data envelopment analysis (DEA), a linear programming method, suggest that fleets with increased energy demand have a higher operational efficiency and, therefore, less space for minimization of operational inputs and environmental impact reductions (Vázquez-Rowe et al 2010b, 2011b.…”
Section: Comparison Between the Assessed Fishing Fleetsmentioning
confidence: 99%
“…The main reason was the great differences in value between processing outputs and between fish species, which meant that the involved fishermen and processors would act to increase the most valuable outputs. Several studies have used mass allocation, including Eyolfsdottir et al (2003), Hospido and Tyedmers (2005), Vázquez-Rowe et al (2010) and Winther et al (2009). Eyjollfsdottir et al (2003 studied trawled cod.…”
Section: Introductionmentioning
confidence: 99%
“…This method enables us to measure an eco-efficiency score with respect to each environmental impact category such as GWP. In contrast, to create a comprehensive eco-efficiency indicator, other papers have proposed data envelopment analysis (DEA)-based eco-efficiency using multiple environmental impacts or life cycle inventory data [56][57][58][59]. A number of studies have confirmed the effectiveness of a combined application of LCA and DEA in aggregate eco-efficiency assessment of agricultural production (e.g., [57,[60][61][62]).…”
Section: Eco-efficiency Measurement Methodologiesmentioning
confidence: 99%